E-Commerce Feasibility Analysis and Strategic Planning to Develop a Small-Medium Enterprise Project in Banking Company - Veronica, Veronica (ComTech: Computer, Mathematics and Engineering Applications, 2018)
The research aimed to identify the problem and the need to develop a small-medium enterprise project in a banking company. The analysis used a literature study, interviews, and observations. The results of the analysis supported the problem and were manifested in the development of information systems in the form of a recommendation for an e-commerce web design. The method consisted of data collection, data analysis and depth interview with Head of E-Commerce Department and Head of Marketing Communication in two days. The result shows that the banking company already uses Bukalapak to enhance their sales and brand. However, based on research, Facebook and Twitter also can be an option to enhance clients’ market access.